Acute encephalitis after COVID-19 vaccination: A case report and literature review. Issue 5 (30th November 2022) - Gao, Jhih-Jian; Tseng, Hung-Pin; Lin, Chun-Liang; Hsu, Ruei-Fong; Lee, Ming-Hsun; Liu, Ching-Hsiung
ABSTRACT: Vaccine-related immune responses are one of the causes of encephalitis. Vaccines against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2, COVID-19) have been administered worldwide due to the ongoing global pandemic; cases of SARS-CoV-2 vaccination-related encephalitis were scarcely reported. An 82-year-old female was diagnosed with acute encephalitis following her first dose of vaccination with mRNA-1273 against SARS-CoV-2. The patient presented with fever and headache five days after vaccination, followed by behavior change 17 days after vaccination. Electroencephalographic recordings revealed focal slow waves in the right frontoparietal regions. Brain MRI revealed the signal change in the right middle and posterior temporal lobe. Cerebrospinal fluid analysis showed mildly elevated protein. She responded well to steroid pulse therapy and made a full recovery. The severity of the immune response following COVID-19 vaccination may be alleviated if adequate treatment is achieved. Physicians must be alert for encephalitis after vaccination to help ensure a favorable outcome.